Implementation of Government Policies in Dealing with Livestock Foot and Mouth Disease (FMD) Outbreaks in Aceh Besar District: Besar Implementasi Kebijakan Pemerintah dalam Penanganan Wabah Penyakit Mulut dan Kaki (PMK) Ternak di Kabupaten Aceh Besar - Ammar, Muhammad; Koesmara, Hendra; Asridiana (Puslatbang KHAN, 2024)
Asridiana2, Muhammad Ammar3 and Hendra Koesmara4 Email: asridosen369@gmail.com ABSTRACT Foot and mouth disease (FMD) is one of the most feared livestock diseases in the world. Clinical symptoms in infected cattle include fever and lesions on the lips, tongue and mouth. The emergence of FMD cases, especially in Aceh, has affected the trade in live cattle and goats in Aceh Besar Regency as one of the districts with the largest population of large livestock (cattle) in Aceh Province. The efforts made by the Aceh Besar District government in dealing with the FMD outbreak through implementing policies issued by the central government have been successful in reducing the spread of FMD to the point of zero cases. The research method used was a literature review approach and data observations in 21 sub-districts spread across the Aceh Besar Regency government area as one of the areas most affected by FMD in Aceh Province. This literature study aims to look at the government's role in handling and preventing the spread of livestock foot and mouth diseaseFrom In all this case, 12,180 livestock were successfully recovered, 24 were conditionally slaughtered, and 28 livestock died due to FMD. Aceh Besar Regency has 21 sub-districts affected by the FMD outbreak. Montasik District recorded the highest number of cases, namely 186,754 cases. As of August 2022, there were 2,189 animals infected with FMD. when the FMD outbreak started to occur, another obstacle felt by farmers was the minimal stock of cattle. This was caused by the closure of cattle entry routes between provinces and districts to prevent the increasingly massive transmission of FMD from cattle to cattle.